A model-independent measurement of the CKM angle γ in partially reconstructed B ± → D * h ± decays with D → K S 0 h + h − ( h = π, K ) - Aaij, R; Abdelmotteleb, ASW; Abellan Beteta, C; Abudinén, F; Ackernley, T; Adeva, B; Adinolfi, M; Adlarson, P; Agapopoulou, C; Aidala, CA; Ajaltouni, Z; Akar, S; et al. (Springer, 2024)
A measurement of CP-violating observables in B± → D*K± and B± → D*π± decays is made where the photon or neutral pion from the D*→ Dγ or D*→ Dπ0 decay is not reconstructed. The D meson is reconstructed in the self-conjugate decay modes, D → KS0π+π− or D → KS0K+K−. The distribution of signal yields in the D decay phase space is analysed in a model-independent way. The measurement uses a data sample collected in proton-proton collisions at centre-of-mass energies of 7, 8, and 13 TeV, corresponding to a total integrated luminosity of approximately 9 fb−1. The B± → D*K± and B± → D*π±CP-violating observables are interpreted in terms of hadronic parameters and the CKM angle γ, resulting in a measurement of γ = (92−17+21)°. The total uncertainty includes the statistical and systematic uncertainties, and the uncertainty due to external strong-phase inputs.